Exploring the stemflow dynamics and driving factors at both inter‐ and intra‐event scales in a typical subtropical deciduous forest. Issue 3 (12th March 2021) - Zhang, Haixia; Fu, Congsheng; Liao, Aimin; Zhang, Can; Liu, Jiufu; Wang, Niu; He, Bin
Abstract: Numerous efforts have been made to understand stemflow dynamics under different types of vegetation at the inter‐event scale, but few studies have explored the stemflow characteristics and corresponding influencing factors at the intra‐event scale. An in‐depth investigation of the inter‐ and intra‐event dynamics of stemflow is important for understanding the ecohydrological processes in forest ecosystems. In this study, stemflow volume ( F V ), stemflow funnelling ratio ( F R ), and stemflow ratio ( F % ) from Quercus acutissima and Broussonetia papyrifera trees were measured at both inter‐ and intra‐event scales in a subtropical deciduous forest, and the driving factors, including tree species and meteorological factors were further explored. Specifically, the F V, F R and F % of Q. acutissima (52.3 L, 47.2, 9.6%) were lower than those of B. papyrifera (85.1 L, 91.2, 12.4%). The effect of tree species on F V and F % was more obvious under low intensity rainfall types. At the inter‐event scale, F V had a strong positive linear correlation with rainfall amount ( G P ) and event duration ( D E ) for both tree species, whereas F R and F % had a positive logarithmic correlation with G P and D E only under high‐intensity, short‐duration rainfall type. F R and F % were mainly affected by wind speed and the maximum 30‐min rainfall intensity under low‐intensity, long‐duration rainfall type. At the intra‐event scale, for both tree species, the mean lag time between the start of rainfall and stemflow was the shortest under high‐intensity, short‐duration rainfall type, while the mean duration and amount of stemflow after rain cessation were the greatest under high‐amount, long‐duration rainfall type. The relationship between stemflow intensity and rainfall intensity at the 5‐min interval scale also depended greatly on rainfall type. These findings can help clarify stemflow dynamics and driving factors at both inter‐ and intra‐event scales, and also provide abundant data and parameters for ecohydrological simulations in subtropical forests. Abstract : Effects of tree species and meteorological factors on stemflow generation depend on rainfall type. Under rainfall types with high amount and high intensity, stemflow intensity has a significant positive correlation with rainfall intensity at the 5‐min interval scale. The lag time between the start of rainfall and stemflow under high‐intensity, short‐duration rainfall type is the shortest, while the duration of stemflow after rain cessation under high‐amount, long‐duration rainfall type is the largest (maximum 4.3 h).